Pengaruh Persepsi Kemudahan, Kepercayaan dan Fitur Layanan Terhadap Minat Mahasiswa Menggunakan Financial Technology (Fintech): Seluruh Mahasiswa Aktif Fakultas Ekonomi Bisnis Dan Pariwisata Universitas Hindu Indonesia - Yuli Artini, Ni Luh Putu; Yuliantari, Ni Putu Yeni (Hita Akuntansi dan Keuangan, 2025)
Financial Technology is an investment alternative that presents options for people who wish to access financial services in a practical, efficient, convenient and economical manner. This study aims to determine the effect of perceived convenience, trust, and service features on interest in using financial technology (fintech). The final sample in this study was 225 responden from the Faculty of Economics, Business and Tourism, Indonesia Hindu University Active who were willing to answer the questionnaire. The analysis technique used is multiple linear regression. The results of the study show that perceived convenience, trust, and service features have a positive effect on interest in using financial technology (fintech).